Number recognition development with number card: Single subject research - Sri Adi Widodo; Istiqomah Istiqomah; Rika Yuliani; Rooselyna Ekawati (Institute of Advanced Engineering and Science, 2022)
Mentally retarded is a mental disorder with an intelligence quotient (IQ) between 55-70, besides those mentally retarded children are only able to think concretely. For this reason, learning mathematics for mentally retarded students requires learning media that can bridge abstract mathematical material with the abilities of mentally retarded children who are only able to think concretely. The objective of this study was to improve the recognition of 1-20 numbers using number cards for students with mild mental retardation. The research used is single subject research method with basic design non reversal. Study subjects were selected based on a purposive sampling technique, as the researcher had to look for subjects with mild mental retardation. Data collection techniques use documentation to find out subjects with mild mental retardation characteristics, and tests to determine the subject's ability to recognize numbers 1-20. The results of this study indicate that the number card media can improve the ability of mild mentally retarded students to recognize numbers 1-20. This can be seen from the average in the baseline phase of 39 with a percentage of the ability to recognize numbers of 33.3%, and in the intervention phase of 74.44 with a percentage of the ability to recognize numbers of 88.89%.